Admissibility, suitability and fundability in the Peruvian civil procedural order - Monroy Palacios, Juan José (2007)
The author develops the outlines for the proper use of the following categories: admissibility, proceeding and sustainability. He sets out from the idea that the common denominator of the three categories is them being decision-making acts, and from the premise that the matter is the procedural situation where the confrontation of the adversaries’ positions usually takes place. To establish the three categories, he distinguishes between the matter in issue and the matter precedent. From this he establishes that the sustainability is the category needed to decide the main aspect and that the origin and admissibility are used to decided that which does not concern the main aspect of the matter. He adds that the distinction between the last two affects the procedural consequences they entail. He also indicates that both inopportuneness and inadmissibility constitute a declaration of invalidity, the former being of irreparable character whereas when it comes to the latter the declaration of invalidity is provisional, that is, reparable, such that when overcome the right to the declaration of the main aspect is born.